Difusi TIK, Kualitas Regulasi, dan Keterbukaan Perdagangan di Negara-Negara G20: Analisis Moderasi - T. Miftahul Afif; Sartiyah Sartiyah (Cendekia Niaga, 2026)
Global economic digitalization is reshaping market integration; however, evidence that information and communication technology (ICT) diffusion consistently increases trade openness remains mixed, and few studies assess regulatory quality as an institutional condition. This study examines the effects of ICT diffusion and regulatory quality on trade openness and tests the moderating role of regulatory quality in G20 countries during the 2002–2022 period. Using secondary panel data from 19 countries with 399 observations, the data were compiled from the World Bank: World Development Indicators (WDI) for trade openness and control variables—economic development, foreign direct investment, and investment—and Worldwide Governance Indicators (WGI) for regulatory quality. ICT diffusion is proxied by a diffusion index on a 0–100 scale. This study applies two-way fixed effects with clustered standard errors, followed by robustness checks using Driscoll–Kraay standard errors and the common correlated effects approach to account for cross-sectional dependence and common shocks. The results show that ICT diffusion is negatively and significantly associated with trade openness, while regulatory quality also tends to have a negative association in the full specification. For Indonesia as a G20 member, these findings suggest that digitalization does not automatically increase trade when it is not supported by the harmonization of digital trade rules, simplified customs procedures, certainty in cross-border data flows, and reduced compliance costs. Therefore, the benefits of ICT for Indonesia’s trade need to be supported by clear and consistent regulatory quality that facilitates cross-border transactions. However, the interaction coefficient between ICT diffusion and regulatory quality is positive, indicating a moderating effect of regulatory quality on the relationship between ICT diffusion and trade openness. This effect suggests that better regulation attenuates the negative impact of ICT diffusion on trade openness. These findings highlight the importance of an integrated policy package: ICT expansion should be accompanied by strengthened regulatory quality, harmonized digital trade rules—such as rules on cross-border data flows, electronic documents, and digital customs—and simplified cross-border trade procedures so that digitalization can more effectively promote trade integration.